Peran Jurusan Green Economy Dapat Mewujudkan Pembangunan Lingkungan Berkelanjutan: Green Economy - Abd Rohman Taufiq; Richo Diana Aviyanti (Owner : Riset dan Jurnal Akuntansi, 2022)
This study aims to provide solutions and references in handling sustainable environmental development. this research method uses a qualitative descriptive phenomenological approach with a literature approach. The results of this study reveal that indonesia cannot be separated from the development of the manufacturing sector which has the function of driving the economy. This must also be balanced with an understanding of the green economy to save the surrounding environment. Experts and literature also reveal that the concept of a green economy is very helpful for the state to preserve natural resources (SDA). The role of the green economy major is very helpful in realizing the welfare of natural resources that can contribute to science. therefore, a green economy major is very much needed in southeast asia, especially the unitary state of the republic of indonesia, Especially Human Resources (HR) who do not understand the importance of a green economy. One of the efforts to save a country is to improve the quality of human resources, especially in this case, human resources who understand the green economy in a sustainable manner. The curriculum that supports this program is the green curriculum, where the curriculum encourages the realization of the indonesian green movement. this scheme builds sustainability through a green economy by realizing various roles. The role of academics aims to create competent human resources in providing scientific literacy and application in the environmental field. Organizations that are directly involved in the green economy, especially environmental issues, are the government, research institutions, and educational institutions.Gr